Klarifikasi al-DarwÃ®sh atas Pandangan Orientalis tentang Kontradiksi Ayat al-Qurâan dengan Kaidah Nahw - Tidjani, Amnah (Mutawatir, 2014)
This paper will examine clarification Muhy al-DÃ®n al-DarwÃ®sh against charges orientalistabout the authenticity of the Koran. Today, these allegations go back voiced by the Egyptian Coptic priest Zakaria Batrousin his book TasÃ¢ulÃ¢t Hawl al-QurâÃ¢n. One of the accused is the assertion that the Koran contains errors and defects in terms of language, as it is considered contrary to the rules nah}w. From here finally Zakaria concludes that the Koran is not the work of God, but a bouquet of Muhammad, because God could do no wrong. What does Zakaria is a fragment of a long journey Orientalist in reviewing the Eastern world, especially the Islamic religion who has written neatly in history. By writing the book IârÃ¢b al-QurâÃ¢n al-KarÃ®m wa BayÃ¢nuh, al-Darwish wanted to prove that what is alleged Zakaria just nonsense. This book is written with a light and easy to understand language readers, especially for the orientalists who lack the ability to understand the science nahw and Arabic literature